SARS-CoV-2-Specific Antibody (Ab) Levels and the Kinetic of Ab Decline Determine Ab Persistence Over 1 Year - Garner-Spitzer, Erika; Wagner, Angelika; Kundi, Michael; Stockinger, Hannes; Ohradanova-Repic, Anna; Gebetsberger, Laura; Schoetta, Anna-Margarita; Gudipati, Venugopal; Huppa, Johannes B.; Kunert, Renate; Mayrhofer, Patrick; Kreil, Thomas R.; et al. (Frontiers in Medicine, 2022)
In a SARS-CoV-2 seroprevalence study conducted with 1,655 working adults in spring of 2020, 12 of the subjects presented with positive neutralization test (NT) titers (>1:10). They were here followed up for 1 year to assess their Ab persistence. We report that 7/12 individuals (58%) had NT_50 titers ≥1:50 and S1-specific IgG ≥50 BAU/ml 1 year after mild COVID-19 infection. S1-specific IgG were retained until a year when these levels were at least >60 BAU/ml at 3 months post-infection. For both the initial fast and subsequent slow decline phase of Abs, we observed a significant correlation between NT_50 titers and S1-specific IgG and thus propose S1-IgG of 60 BAU/ml 3 months post-infection as a potential threshold to predict neutralizing Ab persistence for 1 year. NT_50 titers and S1-specific IgG also correlated with circulating S1-specific memory B-cells. SARS-CoV-2-specific Ab levels after primary mRNA vaccination in healthy controls were higher (Geometric Mean Concentration [GMC] 3158 BAU/ml [CI 2592 to 3848]) than after mild COVID-19 infection (GMC 82 BAU/ml [CI 48 to 139]), but showed a stronger fold-decline within 5–6 months (0.20–fold, to GMC 619 BAU/ml [CI 479 to 801] vs. 0.56–fold, to GMC 46 BAU/ml [CI 26 to 82]). Of particular interest, the decline of both infection- and vaccine-induced Abs correlated with body mass index. Our data contribute to describe decline and persistence of SARS-CoV-2-specific Abs after infection and vaccination, yet the relevance of the maintained Ab levels for protection against infection and/or disease depends on the so far undefined correlate of protection.